Factors that enhance consumer self-protection against online shopping scams - Balakrishnan, Theppan; Abu Bakar, Elistina (Human Resources Management Academic Research Society (HRMARS), 2024)
This study uncovers the factors that empower consumers to protect themselves against online shopping scams. The survey aimed to establish a significant relationship between selfefficacy, social influence, and awareness towards consumer self-protection. A quantitative method was adopted, and a self-administered questionnaire was used for data collection. The data was analysed using the Software Package for Social Science (SPSS). The analysis revealed that self-efficacy and awareness play significant roles in combating online shopping scams. At the same time, social influence was ineffective in enhancing consumer protection against online shopping scams. Both factors can explain 14.7% of the consumer's self-protection against online shopping scams, highlighting the empowering nature of awareness as the main predictor of self-protection. The results indicate that consumers can confidently shield themselves if they possess awareness and self-efficacy and are not controlled by social pressure like their peers. This study, therefore, serves as an empowering framework to boost consumer protection in Malaysia. The findings of this research provide consumers with a sense of control and confidence and can also help consumer associations and the government to increase consumer awareness programs in Malaysia.